Legal Protection of Consumer Personal Data in the Case of Fintech Peer to Peer Lending - Muhammad Abdillah Novaliando (Proceedings Series on Social Sciences & Humanities, 2023)
Fintech is a financial product and service through the incorporation of technology platforms and business models that are innovative, effective and efficient. However, some time ago there was a case of misuse of personal data of fintech users. The offense committed is to disseminate consumer personal data without the consent or knowledge of consumers. The purpose of this study is to determine the legal protection of consumer personal data and legal remedies that can be taken by financial technology consumers if personal data is misused by the organizer. The research method used is normative juridical approach. The results of this study state that, Regulations regarding the protection of personal data to online loan users can refer to POJK No. 1/POJK.07/2013 concerning Consumer Protection in the Financial Services Sector. The regulation contains preventive and repressive protection. Victims of personal data misuse can make legal efforts by way of deliberation and complaints to the Ministry of Communication and Information or OJK (non-litigation) and if it does not resolve consumer disputes can file a civil lawsuit (litigation) on the basis of Unlawful Acts I PMH and request compensation.